Childhood Emotional Neglect and Cardiovascular Disease: A Narrative Review - Salzmann, Stefan; Salzmann-Djufri, Miriam; Euteneuer, Frank (Frontiers in Cardiovascular Medicine, 2022)
Psychosocial factors predict the incidence and progression of cardiovascular disease (CVD). There is accumulating evidence for the importance of childhood maltreatment for the development and progression of both CVD-related risk factors and CVD. However, past research has predominantly focused on active forms of childhood maltreatment such as emotional abuse, physical abuse, and sexual abuse. At the same time, childhood neglect as a relatively silent form of childhood maltreatment received less attention. Childhood emotional neglect is the most common form of neglect. This narrative review summarizes findings on the association between childhood emotional neglect and CVD and potential underlying mechanisms. These mechanisms may involve biological factors (i.e., elevated inflammation, autonomic dysregulation, dysregulated HPA axis, and altered brain development), psychological variables and mental health (i.e., depression and anxiety), and health behaviors (i.e., eating behavior, smoking, drug use, , physical activity) and interpersonal aspects. Evidence suggests that emotional neglect is associated with CVD and CVD risk factors such as obesity, diabetes, inflammation, a dysregulated stress system, altered brain development, depression and other psychological abnormalities (i.e., emotion-regulation difficulties), interpersonal difficulties, and lack of health behaviors. Specific subtypes of childhood maltreatment may be associated with CVD via different mechanisms. This review further encompasses clinical suggestions, identifies research gaps, and has implications for future studies. However, more research with better study designs is desperately needed to identify the exact underlying mechanisms and opportunities for mitigating the negative health consequences of emotional neglect to reduce the prevalence and progression of CVD.